2003
DOI: 10.1136/bmj.327.7428.1384
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism possibly associated with olanzapine treatment

Abstract: study in which indicators of insulin sensitivity were associated with suicide risk. 1 The explanation for the reverse J shaped association seen when diabetes was included as a fifth category alongside insulin resistance may be due to patients with a clinical diagnosis of diabetes developing depression as a result of this diagnosis.We based our assessment of depression on current use of medication and self reports of past diagnoses and current mood rather than clinical assessment with international diagnostic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 5 publications
1
33
0
Order By: Relevance
“…Except for weight lifting, an exercise possibly associated with deep vein thrombosis [54], he had no known risk factors. In another case report massive pulmonary embolism was reported in 25-year-old man with no identified risk factors for VTE, but who had been treated with olanzapine for 3 weeks [35]. Subsequently, the patient also developed pulmonary embolism on two further occasions during treatment with risperidone (3 and 19 weeks after the commencement of treatment, respectively).…”
Section: Venous Thromboembolism and Second-generation Antipsychoticsmentioning
confidence: 96%
See 2 more Smart Citations
“…Except for weight lifting, an exercise possibly associated with deep vein thrombosis [54], he had no known risk factors. In another case report massive pulmonary embolism was reported in 25-year-old man with no identified risk factors for VTE, but who had been treated with olanzapine for 3 weeks [35]. Subsequently, the patient also developed pulmonary embolism on two further occasions during treatment with risperidone (3 and 19 weeks after the commencement of treatment, respectively).…”
Section: Venous Thromboembolism and Second-generation Antipsychoticsmentioning
confidence: 96%
“…The subjects had a variety of clinical and laboratory risk factors. A case of pulmonary embolism was reported in a 28-year-old male 10 weeks after starting treatment with olanzapine due to a psychotic disorder [35]. Except for overweight, no risk factors for VTE were described.…”
Section: Venous Thromboembolism and Second-generation Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, clozapine is the most reported second-generation antipsychotic with epidemiological evidence of DVT [12]. In contrary to clozapine, there are only a few published case reports about the olanzapine-DVT relationship in which the oral form was utilized [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…On the association between VTE and other atypical antipsychotic drugs, 4 casereports (Table II) [24][25][26][27] and 3 previously mentioned studies [4][5][6] were found. The study of Hamanaka et al was based on small numbers (4 patients) 4 and Parkin et al 9 didn't find an increased risk.…”
Section: Psychotropic Drugsmentioning
confidence: 99%